2010
DOI: 10.1029/2009ja015079
|View full text |Cite
|
Sign up to set email alerts
|

Artificial plasma cave in the low‐latitude ionosphere results from the radio occultation inversion of the FORMOSAT‐3/COSMIC

Abstract: [1] Previous studies report unexpected electron density reductions, termed "plasma caves," located underneath the equatorial ionization anomaly (EIA) crests. A radio occultation (RO) observation simulation experiment has been built to evaluate possible biases introduced by the spherical symmetry assumption in the standard (Abel) RO inversion processes. The experiment simulates the electron density profiles and reconstructs the plasma structure of the EIA at low latitudes, where the horizontal gradient is most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 22 publications
4
100
0
Order By: Relevance
“…The RMS increases with increasing altitude over 300 km and reaches about 45% around 500 km. Below 250 km, the estimation error of the N e profile is very large due to the fundamental issue of the Abel inversion (Liu et al, 2010), and the data used in the construction have inherent errors. Such errors might produce a high dispersion and show high RMS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RMS increases with increasing altitude over 300 km and reaches about 45% around 500 km. Below 250 km, the estimation error of the N e profile is very large due to the fundamental issue of the Abel inversion (Liu et al, 2010), and the data used in the construction have inherent errors. Such errors might produce a high dispersion and show high RMS.…”
Section: Resultsmentioning
confidence: 99%
“…Observed N e profiles are accumulated under geomagnetically quiet conditions (K p < 4) from 29 June, 2006, to 17 October, 2009. Since N e profiles are calculated using the Abel inversion with an assumption of spherical symmetry, the errors mainly appear below 250 km around the equatorial ionization anomaly region (Liu et al, 2010), which leads to a negative value of the N e profile in some cases. Therefore, observed N e profiles showing a negative value are not used in the model construction.…”
Section: Methodology Of the Construction Of An Empirical Modelmentioning
confidence: 99%
“…The quality of COSMIC occultation measurements was validated by comparing the data of incoherent scatter radar with those of ionosondes (Lei et al, 2007;Kelley et al, 2009;Sun et al, 2014), which revealed good agreement. Liu et al (2010) and Yue et al (2010) showed that the Abel retrieval provided a accurate ionospheric NmF2 and F2 layer peak height (HmF2) from radio occultation measurements. Hence, COSMIC is a powerful system for global or regional mapping of the ionospheric NmF2 and slab thickness because of its global coverage and high vertical resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists find that the local spherical symmetry assumption in the standard (Abel) RO inversion processes results in systemic biases, especially the EIA (equatorial ionization anomaly) at low latitudes, where the horizontal gradient is most significant (cf. Liu et al, 2010b). Lei et al (2007) indicated that to conduct the Abel inversion, the electron density at the satellite altitude should be assumed.…”
Section: Introductionmentioning
confidence: 99%